Adiponectin and lipid metabolism in skeletal muscle - Bonggi Lee; Jianhua Shao (Elsevier, 2012)
White adipose tissue (WAT) is a key energy depot in humans and most animals. Traditionally, it is believed that WAT passively accumulates triglycerides or releases fatty acids to accommodate systemic energy metabolism. However, recent studies have demonstrated that WAT also actively participates in energy metabolism mainly through its secretion of cytokines and hormones. Therefore, at this time, WAT is recognized as an endocrine organ. Adiponectin is one of the key adipocyte-derived hormones that regulate systemic or tissue lipid and glucose metabolism. In contrast to most other adipocyte-derived hormones, adiponectin increases insulin sensitivity and improves lipid and glucose metabolism. Although the insulin-sensitizing function of adiponectin has been well established, recent studies have demonstrated that adiponectin also regulates metabolism through pathways independent of insulin signaling. Due to the massive tissue mass of skeletal muscle, lipid uptake and subsequent fatty acid oxidation in skeletal muscle have a big impact on maintaining systemic energy homeostasis. Furthermore, adiponectin gene expression is regulated by energy intake. Therefore, adiponectin serves as a coordinator of energy balance amongst WAT, skeletal muscle and other tissues. We summarize the regulatory effects of adiponectin on lipid and glucose metabolism in skeletal muscle. Future research directions have also been proposed.